2015
DOI: 10.1007/s00296-015-3348-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence among patients with rheumatoid disease (RA, AS, PsA) treated with subcutaneous biologics in Germany

Abstract: Patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA) are frequently treated with subcutaneous biologic therapies when disease progresses or when response to synthetic disease-modifying antirheumatic drugs (DMARDs) is inadequate. This study analyzed treatment persistence and treatment patterns for RA, AS, and PsA patients in Germany initiating subcutaneous biologic therapies with and without prior DMARDs use. A retrospective cohort study was conducted using the Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…Patient and physician global disease assessments are combined with 28 swollen and tender joint counts to calculate the Clinical Disease Activity Index (CDAI) from 0 to 76, where < 2.9 is remission, 2.9-10.0 low disease activity, 10.1-22.0 moderate disease activity, and > 22.0 high disease activity [14]. Disease Activity in Psoriatic Arthritis (DAPSA) scores are calculated from joint counts (68 tender/66 swollen), CRP, and patient assessments of disease activity and pain, yielding scores consistent with remission (0-4) or mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), or high (> 28) disease activity [15]. Patients use the Work Productivity and Activity Impairment questionnaire to report the effect of PsA/SpA on work (percentage of hours missed, impairment while at work, and work hours affected) and daily activities [16][17][18].…”
Section: Data Collectionmentioning
confidence: 99%
“…Patient and physician global disease assessments are combined with 28 swollen and tender joint counts to calculate the Clinical Disease Activity Index (CDAI) from 0 to 76, where < 2.9 is remission, 2.9-10.0 low disease activity, 10.1-22.0 moderate disease activity, and > 22.0 high disease activity [14]. Disease Activity in Psoriatic Arthritis (DAPSA) scores are calculated from joint counts (68 tender/66 swollen), CRP, and patient assessments of disease activity and pain, yielding scores consistent with remission (0-4) or mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), or high (> 28) disease activity [15]. Patients use the Work Productivity and Activity Impairment questionnaire to report the effect of PsA/SpA on work (percentage of hours missed, impairment while at work, and work hours affected) and daily activities [16][17][18].…”
Section: Data Collectionmentioning
confidence: 99%
“…Most studies are either from Europe [7][8][9][10][11][12][13][14][15][16] or North America, [17][18][19][20][21][22][23] while studies in Asian populations are scarce. Apart from two Korean studies, 24,25 one Japanese prospective cohort study was identified that analyzed patients who started biologic treatment with infliximab, etanercept, or tocilizumab.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, 20% of discontinuations were the patients' decision with reasons including low level of pain, self-administration of biologics, negative beliefs about treatment, and lack of medical and social support. Finally, Lyu's 2016 study from Germany used electronic medical records to study persistence to subcutaneous biologic therapies among patients with rheumatic disease including 108 patients with AS (36). They reported 1-year discontinuation of 51.9% with mean treatment duration of 228.5 days (36).…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…Finally, Lyu's 2016 study from Germany used electronic medical records to study persistence to subcutaneous biologic therapies among patients with rheumatic disease including 108 patients with AS (36). They reported 1-year discontinuation of 51.9% with mean treatment duration of 228.5 days (36).…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
See 1 more Smart Citation